Birthweight features of the infants of mothers diagnosed with diabetes at different gestational ages in South China from 2014 to 2018: a retrospective study - Xin-xin Huang; Xiu-Min Jiang; Qing-Xiang Zheng; Xiao-Qing Chen; Yu-Qing Pan (BMJ Open)
Objectives The primary purpose was to measure the birth weight of infants of mothers with gestational diabetes (IMGDs) at different gestational ages to develop new reference charts and curves for them. A further purpose was to compare them with those of 159 334 infants in China to provide more accurate reference charts for the diagnosis of suspected abnormal birth weight of IMGDs. The final purpose was to evaluate the key periods for such mothers to control their weight in line with the difference of fetal weight of each two neighbouring gestational ages.Setting A specialised hospital in South ChinaParticipants IMGDs born here from January 2014 to December 2018.Primary and secondary outcome variables Birth weight, gestational ages of IMGDs, gender and year of birth.Results Data of 14 311 singleton live births at the gestational weeks 25–42 here were collected. The proportions of low birth weight, normal birth weight and macrosomia were 7.26%, 87.04%, and 5.70%, respectively. The proportions of small for gestational age, appropriate for gestational age and large for gestational age were 5.69%, 84.42% and 9.89%, respectively. In the macrosomia group, the mean of all birth weight in 2017 decreased for the first time since 2014. Both the means of birth weight of male infants at gestational weeks 36–41 and of female at weeks 38–40 were greater than that of the 159 334 infants. The increase of each weekly mean of IMGDs at gestational weeks 27–31 and 33–35 was >10% compared with the former. Based on this, new reference charts of birth weight for IMGDs in terms of different gestational age and gender were formulated.Conclusion These charts may be applied as reference for more accurate diagnosis and quick treatment of abnormal birth weight. This study showed that the identification of key periods for fetal weight gain was helpful for the management of the weight of women with gestational diabetes.